Causes of stillbirth according to different gestational ages - Jindal, Aditi; Thakur, Rama; Minhas, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Stillbirth is one of the most common yet the most poorly studied adverse outcome of pregnancy. Objective of present study was to determine the risk factors and prevalence of stillbirth at Department of Obstetrics and Gynecology, Kamla Nehru State Hospital, for Mother and Child, Indira Gandhi Medical College, Shimla, Himachal Pradesh. Methods: A prospective non-interventional study was conducted with effect from 1st August 2015 to 31st July 2016, during which all the intrapartum and antepartum stillbirths were enrolled. Results: During the study period total number of stillbirth were 94 and the total number of live births were 6412, giving a stillbirth rate of 14.66/1000 live births. The perinatal mortality was 22.1/1000 births. The most common cause of stillbirth as revealed in the study was hypertensive disorder. Conclusions: The stillbirth rate in the study was higher than the stillbirth rate of developed countries. Improvement of socioeconomic conditions, literacy and health education among women will definitely be important to curb the staggeringly high stillbirth rate, but the need of the hour is to deploy adequate number of dedicated skilled providers.